Allergic contact dermatitis caused by topical antiacne drugs. Issue 4 (July 2015) - Veraldi, Stefano; Brena, Michela; Barbareschi, Mauro
<x xml:space="preserve">Abstract</x> Acne is a chronic inflammatory disease for which a long-lasting therapy, very often with topical drugs, is necessary. Despite the fact that several topical antiacne drugs (in particular, tretinoin, benzoyl peroxide, clindamycin and erythromycin) are used for many years, often on broad skin surfaces and for long periods of time, their potential for contact sensitization is low. Their potential for phototoxic and photoallergic reactions is also low. Much more frequent is irritant contact dermatitis caused by some of these drugs, in particular, retinoids and benzoyl peroxide, for which the short contact therapy has been recently suggested.